Case Report: Combining liver partition and portal vein ligation after thrombectomy for tumor isolation (CLAPT) to treat advanced hepatocellular carcinoma with portal vein tumor thrombosis - Jin, Zongrui; Wu, Guolin; Xu, Banghao; Wang, Jilong; Zhu, Hai; Guo, Ya; Peng, Minhao; Peng, Tao; Wen, Zhang (Frontiers in Surgery, 2022)
ABSTRACT Background: Primary liver cancer is the third leading cause of cancer-related deaths worldwide in 2020, and hepatocellular carcinoma (HCC) is the major pathological type. Patients with HCC complicated with portal vein tumor thrombosis (PVTT) have a poor prognosis, and controversies regarding treatment options exist among international scholars. Patients with VP4 or Cheng’s type III are generally considered ineligible for surgical treatment. Methods: We retrospectively analyzed three cases of HCC with PVTT who underwent a novel modified surgical procedure. The procedure included portal vein thrombectomy and portal vein ligation with liver parenchymal separation for the resection of the tumor thrombus involving the main portal vein trunk and for the isolation of the giant tumor. The three cases were then treated with targeted drugs postoperatively. Results: One case developed acute renal failure in the perioperative period, and the renal function gradually recovered after the treatment. The two remaining cases recovered uneventfully postoperatively. The prognosis of the three patients was encouraging. Only one patient died of lung metastasis after 13 months, and the remaining patients were still alive after 41 and 21 months. Conclusions: We provide a new possible surgical option for patients with advanced HCC with PVTT. The surgical procedure was inspired by associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) and portal vein thrombectomy. The survival time was significantly prolonged after the patients underwent thrombectomy, tumor isolation, and postoperative nonsurgical treatment. Hence, the combination of liver partition and portal vein ligation after thrombectomy for tumor isolation (CLAPT) has potential for the treatment of advanced HCC with PVTT.